Dampak Lingkungan Stunting Dan Perekonomian - Rully Angraeni Safitri; Dewi Puspitasari; Fajar Ramadhan Saputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Stunting is complex and involves various factors such as access to nutritious food, feeding practices, sanitation, maternal and child health care, family economics, and the physical environment. To overcome stunting and its impacts, a cross-sectoral approach is needed which includes improving access to nutritious food, improving sanitation, health education, access. The community service program is carried out with a community approach, so that it is right on target. The method used in this community service is community service with a community service method, combining the essence and practical analysis of many things, scientifically accurate and authentic sources. This can reduce a country's labor capacity and hinder long-term economic growth. Limited education can limit their access to better, higher-paying jobs in the future